Stomach Content Analysis of Pristolepis grootii Bleeker from the Lubuk Siam Lake, Siak Hulu Sub-regency, Kampar Regency, RiauProvince - Fuad Ardiansyah Siregar; Ridwan Manda Putra; Windarti Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractPristolepis grootii is one of freshwater fishes that inhabit the Lubuk Siam Lake in the Kampar Regency. The information on the feeding habit of that fish, however, is rare. To understand the type of food consumed by that fish, a research has been conducted in January to February 2020. Sampling was conducted once/ two weeks interval for a two months period. There were 96 fishes captured, but 22 of them had empty stomach and they can not be used for stomach content analysis. Theanalysis was conducted using avolumetric method. Stomach content wasanalyzed as a basis to calculate thePreponderance Index (PI).Results shown thatthe main food of the fish in Lubuk Siam Lake was plant (PI 55.50%) and insect (PI 40.50%), another type of food was fish, crustacean  and unidentified debris which classified as additional food (PI was 2.67%, 1.02% and 0.32% respectively). Data obtained indicate that this fish can be categorized as omnivore.Keywords : feeding habit, food habit, Preponderance Index,Oxbow Lake